2023
DOI: 10.1021/acschemneuro.3c00176
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Protects Dopaminergic-like Neurons against Paraquat- and Maneb-Induced Cell Death through Safeguarding DJ-1CYS106 and Caspase 3 Independently of Cannabinoid Receptors: Relevance in Parkinson’s Disease

Miguel Mendivil-Perez,
Andrea A. Felizardo-Otalvaro,
Marlene Jimenez-Del-Rio
et al.

Abstract: Parkinson's disease (PD), a progressive neurodegenerative movement disorder, has reached pandemic status worldwide. This neurologic disorder is caused primarily by the specific deterioration of dopaminergic (DAergic) neurons in the substantia nigra pars compacta (SNc). Unfortunately, there are no therapeutic agents that slow or delay the disease progression. Herein, menstrual stromal cell-derived dopamine-like neurons (DALNs) intoxicated with paraquat (PQ 2+ )/maneb (MB) were used as a model system to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(118 reference statements)
0
0
0
Order By: Relevance
“…Our findings demonstrated that caspase-3 activity decreased in SH-SY5Y cells under OGD/R conditions treated with DDS-CBD, showing a decrease in apoptosis. This event is consistent with current findings where reduced or null expression of caspase-9 and caspase-3 as observed in an in vitro model of cerebral ischemia, Alzheimer's [50,58,59], as well as cells treated with hydrogen peroxide [60], after exposure to CBD. On the other hand, it has also been observed that DDS is an antiapoptotic drug, as revealed in previous studies in which the administration of DDS decreased the activities of caspase-9 and caspase-3 in models of focal cerebral ischemia [29] and spinal cord injury in rats [61].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings demonstrated that caspase-3 activity decreased in SH-SY5Y cells under OGD/R conditions treated with DDS-CBD, showing a decrease in apoptosis. This event is consistent with current findings where reduced or null expression of caspase-9 and caspase-3 as observed in an in vitro model of cerebral ischemia, Alzheimer's [50,58,59], as well as cells treated with hydrogen peroxide [60], after exposure to CBD. On the other hand, it has also been observed that DDS is an antiapoptotic drug, as revealed in previous studies in which the administration of DDS decreased the activities of caspase-9 and caspase-3 in models of focal cerebral ischemia [29] and spinal cord injury in rats [61].…”
Section: Discussionsupporting
confidence: 93%
“…All of these actions explain DDS-CBD's potential neuroprotective effectiveness in the OGD/R model, as seen in Figure 7. 9 and caspase-3 as observed in an in vitro model of cerebral ischemia, Alzheimer's [50,58,59], as well as cells treated with hydrogen peroxide [60], after exposure to CBD. On the other hand, it has also been observed that DDS is an antiapoptotic drug, as revealed in previous studies in which the administration of DDS decreased the activities of caspase-9 and caspase-3 in models of focal cerebral ischemia [29] and spinal cord injury in rats [61].…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, combined exposure to PQ + MB for 12 h decreased the MMP. Our findings align with previous studies indicating that the combination of PQ and MB reduces the MMP in dopamine-like neurons and in human nerve-like cells. , The MMP has an essential role in maintaining cellular homeostasis, and a drop of MMP may induce loss of cell viability and apoptosis . The toxicity of several xenobiotic compounds can have either a primary or a secondary effect on mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, it has been reported that MB potentiate PQ toxicity in in vivo and in vitro experimental conditions . Exposure to PQ plus MB in combination causes disruption of mitochondrial membrane potential (MMP) and induced oxidative stress in dopaminergic-like neurons . Moreover, exposure to PQ plus MB induces ferroptosis in SH-SY5Y cells, which was linked to NADPH oxidase activation …”
Section: Introductionmentioning
confidence: 99%
“…Our data obtained in SH-SY5Y cells support reports showing the neuroprotective effects of CBD in other in vitro models of Parkinson's disease. Thus, CBD protected the neural cells from apoptosis in vitro menstrual stromal cell-derived dopamine-like neurons (DALNs) exposed to paraquat, and this effect was accompanied by inhibition of caspase-3 activity [39]. CBD also reduces cell damage of undifferentiated and retinoic acid differentiated SH-SY5Y cells exposed to 1-methyl-4-phenylpyridinium (MPP+)-A neurotoxin which inhibits mitochondrial complex I, decreases ATP level and enhances ROS production [23,40].…”
Section: Discussionmentioning
confidence: 99%